The Multiple Roles of Vitamin D in Human Health. A Mini-Review - Boucher, Barbara J. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2011)
Vitamin D is a hormone precursor, originally provided by ultraviolet light-induced skin synthesis of cholecalciferol but, with modern lifestyles, humans depend on dietary intake [mainly as ergocalciferol]; adequate intakes are essential for musculo-skeletal health, the ‘classical’ benefits of this vitamin, modulated by the activated hormonal metabolite, calcitriol. Most other tissues also contain vitamin D receptors and it's activating enzyme. Hypovitaminosis D is associated with many disease risks and many protective mechanisms are known that explain this; in vitro and in vivo repletion or supplementation activating such mechanisms [e.g. in inflammation, atherosclerosis & malignancy]. This review outlines knowledge on the roles of vitamin in reducing all-cause mortality and ameliorating disease [including metabolic syndrome, insulin resistance and secretion, diabetes, hypertension, cardiovascular disease, autoimmunity, arthritis, multiple sclerosis, periodontal disease, inflammatory bowel disease, asthma and respiratory infections, tuberculosis, nonalcoholic fatty liver disease, polycystic ovary syndrome and fertility, wound healing, psoriasis and sepsis]. Interactions of vitamin D with calcium & vitamin A and variation in effects with genetic polymorphisms are referred to. Reasons for the continuing high prevalences of vitamin D insufficiency world-wide and current difficulties in defining both vitamin D status and adequate repletion are discussed. It is suggested that whilst calcitriol analogues may have increasing roles in treatment, adequate vitamin D repletion at the population level is likely to provide a very cost-effective measure for health promotion. However, adequate randomized controlled trials are needed before larger doses than currently used are considered for long-term use at the population level.
Keywords: effects